An Analysis of Translation Techniques of Collocation in A Child Called ‘It’: One Child Child’s Courage to Survive - Sulaiman, Sulaiman; Rahmawati, Irma (Aksara: Jurnal Bahasa dan Sastra, 2025)
The objective of this research is to find translation techniques and the types of collocation in the novel A Child Called ‘It’: Once Child’s Courage to Survive. The limitation in this research is only to examine the analysis of collocation translation. The gap of this study is that there is still a misunderstanding in translating collocation and investigating how collocation is actually translated. This research used the theory of Molina and Albir (2002) for the technique of translation and the theory of McCarthy and O‘Dell (2017) for the collocation. This research used a descriptive qualitative method. The data were collocations in the novel A Child Called ‘It’: Once Child’s Courage to Survive in two versions, English as the source text and Bahasa Indonesia as the target text. From 18 techniques. There are 11 techniques applied in the data, which are adaptation, amplification, borrowing, calque, description, discursive creation, established equivalent, literal translation, modulation, reduction, and variation. In addition, there are six types of collocation found, which are adjectives and nouns, nouns and verbs, nouns and nouns, verbs and expressions with prepositions, verbs and adverbs, adverbs and adjectives. This research is expected to be useful for further research and could help improve understanding in translation.Keywords: translation, translation technique, collocation